Financial Report Analysis with Financial Ratios and Company Valuation at PT BBS - Rusli, Yohanes Mardinata (Eastasouth Journal of Effective Community Services, 2025)
A company's ability to generate profits is key to its success, as profitability is a component of financial reporting used to assess a company's performance, particularly from a financial perspective. This will impact the company's continued growth and cooperation with other companies. This Community Service Program was held on Friday, December 22, 2023, at PT. Bangun Berlian Solusindo (PT. BBS) – via online class using Zoom. The Community Service Program went smoothly and smoothly according to the plan outlined in the Community Service (PkM) proposal. PT. BBS employees gained new knowledge and skills regarding Financial Statement Analysis, starting with Financial Ratios and Company Valuation.